Physical activity in a large sample of adults with intellectual disabilities - Barnes, T.; Howie, Erin; McDermott, S.; Mann, J. (Human Kinetics Inc, 2013)
Background: Few studies have documented physical activity (PA) and overweight and obesity in adults with intellectual disabilities (ID) using both self-report and objective methods. We sought to characterize PA in adults with ID and examine the associations between self-reported activity types, objectively-measured PA, and objectively-measured body mass index (BMI). Methods: Self-reported PA and BMI were measured on 294 adults with ID. Accelerometry was collected on 131 of those participants. Differences in BMI and accelerometry by demographic factors and activity types were examined. Results: Among the participants, 79.6% were overweight or obese and 23.7% met recommended PA guidelines. The mean amount of moderate-to-vigorous PA (MVPA) per week was 108.6 minutes. The most common activities reported were walking (53.7%) and inside chores (42.5%). Twenty-six percent reported no activity. Biking and jogging/running was associated with lower BMI. Self reports of playing basketball, softball, and outside chores were associated with increased MVPA. Conclusion: In this sample of adults with ID, most participants were overweight or obese and PAlevels were below national averages. Select self-reported activities and greater objectively measured PA were associated with lower BMI.